EFFECT OF WORK MOTIVATION, WORK ENVIRONMENT AND EDUCATION ON EMPLOYEE EFFECTIVE COMMITMENT (case study at Permata Ananda Autism Therapy Center, Banguntapan, Bantul, Yogyakarta 55198) - Abd Jalil; Prayekti Prayekti; Kusuma Chandra Kirana (Universitas Muhammadiyah Makassar, 2021)
This study aims to find out if work motivation, work environment, and education affect the effective commitment of employees of Permata Ananda Autism Therapy Center. The population in this study used all employees of Permata Ananda Autism Therapy Center which numbered 45 employees. Sample withdrawal method is non probability sample with saturated samplingtechnique, data collection is done through questionnaires and get the results of 45 respondents as samples. The results in this study show that; (1) Work Motivation has no partial effect on employees' effective commitment, (2) Work Environment partially affects employees' effective commitment, (3) education partially affects employees' effective commitment, (4) Work Motivation, Work Environment, and Education affect simultaneously.